Limnocentropus kritsaneepaibooni new species (Limnocentropodidae: Trichoptera) from Shan State, Myanmar, with faunistic data for the family - Laudee, Pongsak; Malicky, Hans (Zootaxa, 2016)
A new species of Limnocentropus, Limnocentropus kritsaneepaibooni n. sp. from Keng Tung Province, Shan State, Myanmar, is described and figured. Three other, previously described species of Limnocentropus are newly recorded for Myanmar, including L. apollon Malicky 1999, L. sammuanensis Malicky & Chantaramongkol 1989, and L. siribhumensis Malicky & Chantaramongkol 1989, resulting in 7 species of the family found in Myanmar.